THE EFFECT OF CHOOSING ELECTRON BEAM ENERGY AND IOERT TREATMENT APPLICATOR SIZE ON BEAM FLATNESS AND BEAM SYMMETRY PARAMETERS BY USING MONTE CARLO METHOD - ILHAM RAMADHAN (NIM : 10214062), NUZUL
The IOERT (Intraoperative Electron-beam Radiation Therapy) method is a cancer treatment method that uses a combination of surgical techniques and radiation techniques. The IOERT method can be successfully categorized when it can be able to distribute homogeneous doses of radiation to targeted tumors. In this study, the optimum electron beam energy and the applicator size of the IOERT method were performed with beam symmetry and beam flatness and parameters on the 1-D dose distribution curve (PDD and dose profile) generated. This is done because the homogeneity of a beam can be measured from beam flatness and beam symmetry. Electron beam energy optimization and IOERT treatment applicator size were performed using Monte Carlo method with EGSnrc software program package. In this study the electron beam energy to be optimized is 4, 6, 8, 10, and 12 MeV, and the size of the applicator IOERT diameter to be optimized in the range of 3-10 cm. In this study also selected source files that meet the form of Gaussian distribution that represents the direction of motion and position of the electron beam with the width of FWHM set at 2 mm. Electron energy for IOERT is greater than 0.68% to 5.37% of other treatment methods. Electron beam energy and large applicator diameter sizes will cause worse heterogeneity of the beam.